Do firms have leverage targets? Evidence from acquisitions - Harford, Jarrad; Klasa, Sandy; Walcott, Nathan (Journal of Financial Economics, 2009)
In the context of large acquisitions, we provide evidence on whether firms have target capital structures. We examine how deviations from these targets affect how bidders choose to finance acquisitions and how they adjust their capital structure following the acquisitions. We show that when a bidder's leverage is over its target level, it is less likely to finance the acquisition with debt and more likely to finance the acquisition with equity. Also, we find a positive association between the merger-induced changes in target and actual leverage, and we show that bidders incorporate more than two-thirds of the change to the merged firm's new target leverage. Following debt-financed acquisitions, managers actively move the firm back to its target leverage, reversing more than 75% of the acquisition's leverage effect within five years. Overall, our results are consistent with a model of capital structure that includes a target level and adjustment costs.